2022
DOI: 10.3389/fnut.2021.799095
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Dietary Antioxidant Micronutrients and Cardiovascular Disease in Adults in the United States: A Cross-Sectional Study

Abstract: Background: Antioxidant micronutrients represent an important therapeutic option for the treatment of oxidative stress-associated cardiovascular diseases (CVDs). However, few studies have evaluated the relationship between the levels of multiple dietary antioxidants and CVDs.Objective: The study therefore aimed to evaluate associations between dietary antioxidants and total and specific CVDs among a nationally representative sample of adults in the US.Design: In total, 39,757 adults (>20 years) were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
0
12
3
Order By: Relevance
“…Studies have shown that selenium-rich Brazil nuts can improve oxidative stress by regulating GPx activity and the expression of Nrf2-related genes ( 65 ). In addition, selenium is a component of dietary antioxidants and increasing dietary antioxidant intake may not only reduce the risk of stroke but also improve the prognosis of stroke patients ( 66 , 67 ). Although many studies have demonstrated the beneficial effects of selenium on stroke, a balanced diet (containing fruits, vegetables, legumes, whole grain cereals, nuts and seeds) naturally rich in antioxidant foods such as selenium may be a safer approach until the mechanistic effects of selenium and antioxidant supplement use on stroke are elucidated ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that selenium-rich Brazil nuts can improve oxidative stress by regulating GPx activity and the expression of Nrf2-related genes ( 65 ). In addition, selenium is a component of dietary antioxidants and increasing dietary antioxidant intake may not only reduce the risk of stroke but also improve the prognosis of stroke patients ( 66 , 67 ). Although many studies have demonstrated the beneficial effects of selenium on stroke, a balanced diet (containing fruits, vegetables, legumes, whole grain cereals, nuts and seeds) naturally rich in antioxidant foods such as selenium may be a safer approach until the mechanistic effects of selenium and antioxidant supplement use on stroke are elucidated ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with those of Kodali et al ( 1 ): Copper might reduce the risk of ischemic heart disease. Yin et al ( 45 ) showed that high levels of antioxidant micronutrients in the diet were correlated with reduced cardiovascular disease morbidity; levels of iron, zinc, and copper were inversely and non-linearly correlated with cardiovascular diseases. Therefore, trace minerals might have the ability to prevent cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the crucial role of Se in the cellular antioxidant defense system, therapeutic strategies involving Se supplementation for the treatment of certain diseases have been underway for many years [77,78]. Recently, this practice has achieved promising results in the prevention and treatment of metabolic diseases, including CHD, HT, NAFLD, and T2DM [6,[79][80][81][82].…”
Section: Se Levels and Metabolic Diseasesmentioning
confidence: 99%